Prevalence of bovine brucellosis in slaughtered cattle and barriers to better protection of abattoir workers in Ibadan, South-Western Nigeria. (2017)
Brucellosis is a neglected zoonosis of public health importance. This study was conducted to determine the prevalence and risk factors of brucellosis among slaughtered cattle as well as challenges to the protection of abattoir workers in Nigeria. Methods: A slaughterhouse study was conducted in a major abattoir in Ibadan from March to August, 2013. To diagnose brucellosis, serum samples from 1,241 slaughtered cattle were tested using Rose-Bengal test (RBT) and competitive enzyme-linked immunosorbent assay (cELISA); again, 57 milk samples were tested with milk ring test (MRT) and indirect ELISA (iELISA). Furthermore, a survey on the usage of personal protective equipment (PPE) and challenges to its use by abattoir workers was done. Data were analysed using Stata 12. Results: Seroprevalence by RBT was 7.8%; 77.3% (75/97) of these were corroborated by cELISA. Prevalence in milk samples by MRT and indirect ELISA were 33.3% and 3.5%, respectively. Sex (OR: 2.5; 95%CI:1.3-4.5) was the factor significantly associated with Brucella seropositivity. None of the abattoir workers used standard protective overalls; while, 99.6% of the meat handlers and 84.1% of the butchers worked barefoot. Most of the workers (75.7%) wore no protective gloves. The respondents agreed that provision of free PPE and sanctions against non-users would encourage its use. Conclusion: Our findings indicate moderate prevalence (7.8%) of bovine brucellosis with sex of cattle being a risk factor. A notable barrier to better protection of abattoir workers against brucellosis is perceived inconvenience arising from use of gloves. Therefore, preventive and control measures against brucellosis must include education and use of PPE among abattoir workers.